The gigantic ants & other cases eaudiobook - Simon, Seymour (Einstein Anderson, 2000)
Life in sixth grade is full of challenges and goofy jokes for Adam "Einstein" Anderson. His friends, family members, and enemies love to test his scientific knowledge. Can anyone outsmart him? Einstein's friend Stanley believes he can raise gigantic ants to help people work, but is it possible? Margaret, Einstein's best friend, wonders if a block of ice can be sliced through without making two pieces. When a professor claims his invention can stop hurricanes, is he telling the truth or does he just want money? Even Pat, the class bully, thinks he can outsmart Einstein. But Einstein tells Pat, "The next time you get a bright idea, it will be beginner's luck." With this book, author Seymour Simon shows that what seem like difficult problems often have simple, fascinating solutions. Readers will enjoy learning the science "tricks" in these ten stories. Narrator Johnny Heller creates an Einstein who is both clever and silly.